2013
DOI: 10.1111/jfr3.12065
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant factors of flood insurance demand for flood‐hit residential properties: a case for Malaysia

Abstract: Securing flood insurance for real estate properties in flood-hit areas is rather uncertain under the Malaysian scenario. This study attempts to identify the demand-side factors of flood insurance in coastal residential areas, and to examine how these factors differentiate between two groups of respondents, namely flood insurance purchasers and non-purchasers, using discriminant analysis. Tests using Wilks' lambda, eigenvalues, canonical correlation, functions at group centroids, and classification accuracy hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Studies specific to Malaysia have shown that rapidly increasing flood events in recent decades are due to unrestrained occupation of rivers by human activities, destruction of forest and extreme weather events caused by climate change (Aliagha et al, 2015). Statistics show an average of 143 floods per year since 2001, of which more than 90% are flash floods (Mohd Anip and Osman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies specific to Malaysia have shown that rapidly increasing flood events in recent decades are due to unrestrained occupation of rivers by human activities, destruction of forest and extreme weather events caused by climate change (Aliagha et al, 2015). Statistics show an average of 143 floods per year since 2001, of which more than 90% are flash floods (Mohd Anip and Osman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, past researches showed that flood is the most common disaster affecting a number of areas especially the low area since 1920s. Past researches stated that almost 9% of the total disaster is caused by the widening of the area while almost 22% of the total population is directly affected by floods ( Salleh et al, 2013;Othman et al, 2014;Aliagha et al, 2015;Khalid & Shafiai, 2015;Tan et al, 2015). Indeed, the flood disaster is expected to keep rising in line with the increase of migration from the rural residents to the cities, changes in the structure of soil which is caused by uncontrolled development, poverty and other factors that threaten the floodplain areas (Mustaffa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the flood disaster is expected to keep rising in line with the increase of migration from the rural residents to the cities, changes in the structure of soil which is caused by uncontrolled development, poverty and other factors that threaten the floodplain areas (Mustaffa et al, 2014). Floods often occur in Malaysia due to the increase in the frequency of rainfall and the rise of the level of the sea in certain parts of the country (Aliagha et al, 2015). Furthermore, the condition of climate in Malaysia is experiencing rainfall with the average of approximately 2,500 mm a year in Peninsular Malaysia, 3,000 mm a year in Sabah and 3,500 mm a year in Sarawak (Tahir, 2009;Khalid & Shafiai, 2015;Tan et al, 2015) making it as a common natural disaster in Malaysia (Othman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Malaysia, flood occurs nearly every year during the monsoon season and is considered as a regular natural disaster in the country. Given Malaysia's geographical location, we face a heavy and regular rainfall during the local tropical wet season from October to March each year and flood is a natural result of this cyclical monsoons [1]. As stated by Chan [2], when flood happens, they caused millions of Ringgit in damages, the loss of life and property along with agricultural and livestock devastation.…”
Section: Introductionmentioning
confidence: 99%